Static and dynamic mechanical responses of organic shales under combined temperature and confining pressure conditions - Hu, Laidong; Dong, Xuguang; Wang, Xiaoyang; Wang, Yang (Frontiers in Earth Science, 2025)
IntroductionRocks are subjected to pressure and temperature underground. In situ mechanical properties of organic shales are of principal importance in unconventional reservoir exploration and production, CO2 sequestration, and geothermal energy exploitation.MethodsTo better understand the combined effects of temperature and confining pressure on anisotropic mechanical properties, we perform a series of triaxial tests on two pairs of organic shales at temperatures ranging from 25 °C to 105 °C and confining pressures varying from 5 MPa to 45 MPa. Both static and dynamic mechanical properties (Young’s modulus and Poisson’s ratio) are investigated.ResultsThe experimental results suggest that the increasing confining pressure and temperature increase and decrease dynamic Young’s moduli, respectively, but jointly increase the apparent static Young’s moduli. The temperature effect on dynamic properties is weakened, while that on static properties is increased by the increasing confining pressure. In contrast, an increase in temperature increases confining pressure effects on both dynamic and static properties. Additionally, due to the existence of bedding planes, compaction and thermal expansion caused by the increasing confining pressure and temperature are anisotropic. With increased confining pressure, the anisotropy of dynamic properties decreases while that of static properties increases, with a tendency to approach each other at the maximum confining pressure. However, the anisotropies of dynamic and static properties tend to diverge from each other with increasing temperature. Moreover, although dynamic properties are characteristically greater than static ones, the correlation coefficients between dynamic and static Young’s moduli are highly affected by the applied confining pressure and temperature. Ignoring either effect would result in an overestimation of the correlation coefficient.DiscussionThe findings provide an innovative approach to jointly evaluate the effects of temperature and confining pressure effects on dynamic–static correlations in anisotropic shales, although limited samples and measurement constraints might create limitations in geoengineering applications.